Government political structure and violent death rates: A longitudinal analysis of forty-three countries, 1960–2008. (July 2019) - Marotta, Phillip; Lee, Bandy X.; Blay-Tofey, Morkeh; Kim, Clara H.; Schuder, Kelsey K.; Lee, Grace; Gilligan, James
Abstract: Objectives: Currently, little is known regarding the effect of regime type on mortality on a global level. The purpose of this study is to examine the effect of regime type on the rates of violent deaths (homicide, suicide, and combined rates). Methods: Three measures of democracy were used to quantify regime type, the independent variable. Homicide and suicide rates were obtained from the World Health Organization. Multivariate conditional fixed-effects models were run to examine associations between regime characteristics and logged rates of homicide, suicide, and violent deaths. Models were adjusted for unemployment and economic inequality. Results: Nations that scored higher on democracy indices, especially emerging democracies, experienced increased mortality due to violence. Homicide and suicide were divergent, showing a different time course and decreasing statistical power as a combined variable. Unemployment and inequality were associated with higher violence-related mortality. Conclusions: Homicide and suicide appear to be more prevalent in democracies. Future analyses should examine which aspects of democracies lead to higher rates of violent death and should seek to use independently collected mortality data.